Fuzzy Comprehensive Evaluation on the Effect of Measures Operation for Oil-Water Well - Zhi-Bin Liu; Wei Qing; Xin-Hai Kong (Advances in Fuzzy Systems)
The measures operation is an important component of borehole operation, and the operation effects directly affect the increase of oil and gas production. In perspective of the present reality of borehole operation company, the authors analyze the commonly used type of measures on the oil field, summarize six indicators to evaluate the measures operation effect, and give the quantitative calculation method for six evaluation indicators. Through the experts grading method, we can obtain all the weights of indicators and then establish the fuzzy comprehensive evaluation model of operation effect of measures. The evaluation model can be used to evaluate the operation effect of single well, oil block, or the branch company. Based on the actual data of measures operation of a branch company, using the fuzzy comprehensive evaluation approach to evaluate each block in the branch company, this paper obtained the same conclusion as the qualitative analysis.